The dark horse book of horror ebook - Busiek, Kurt (The Dark Horse Book of Horror., 2021)
Explore the dark corners of the horror genre with this collection of spooky tales of witchcraft, ghosts, and the risen dead! Originally collected as a hardcover, these stories from the likes of Mike Mignola, Evan Dorkin, Jill Thompson, Gary Gianni, Robert E. Howard and more first appeared in the Dark Horse Book of Monsters, the Dark Horse Book of Witchcraft, the Dark Horse Book of Hauntings, and the Dark Horse Book of the Dead. Now available for the first time in paperback, these haunting shorts have lost none of their spine-tingling genius!